Applied asymptotics : case studies in small-sample statistics - Brazzale, A. R. (Alessandra R.) (Cambridge series on statistical and probabilistic mathematics., 2007)
First practical treatment of small-sample asymptotics, enabling practitioners to apply new methods with confidence.